(untitled) (Research, Society and Development, 2020)
To characterize the sociodemographic and clinical profile of Bone Marrow Transplant in two centers in Brazil and one in Spain. Cross-sectional study conducted with 40 respondents appropriate to the inclusion criteria. Data were collected from March 2016 to October 2017. We found a differentiation of gender and age group between countries: predominance of females (25%); age group from 21 to 50 years (30%) in Brazil and male (37.5%); age group 51 to 70 years (35%) in Spain. There was similarity, respectively, of race / white color, 1st grade education, married marital status, Catholic religion, income from 1 to 2 minimum wages, primary disease and leukemia. highest frequency of Halogen transplantation in Spain (37.5%). The study had a strengthening advance in nursing actions, providing them with tools for organization, planning and decision making, and for promoting care with patients and their families.